Transmissão vertical e horizontal de parasitas usando autômatos celulares probabilísticos - Rodrigues, Lázaro Luiz Fratoni (2011)
wide range of pathogens are transmitted by a combination of horizontal and vertical transmission; among these are microsporodians, helminths, bacteria and viruses of plants and animals, including important human pathogens such as HIV, HTLV-1, cytomegalovirus, several hepatitis viruses and herpes simplex [Proc. R. Soc. Lond. B 260: 321-327]. In this work, the vertical parasite spreading from parent to offspring and horizontal transmission through infection in a population of moving individuals are discussed using a probabilistic cellular automata implemented on a square lattice. In our model, we generalize the automata proposed in [J. Phys. A : Math. Gen. 27: 1585-1597] to include the vertical transmission. The local rule consists of two subrules: the first one, applied synchronously, models infection, birth and death processes; the second, applied sequentially, describes the motion of individuals. In this model, endemic states may occur (susceptible and infected individuals coexisting) or a disease-free state (without infected). It is worth mentionins that a state in which the entire population becomes infective is possible in the case of perfect vertical transmission, i.e. infected parents give birth only to infected offspring. Moreover, the stability of these states may be analised using a mean-field approximation or grafically verified from the numerical simulations.